Celebrity endorsements, self-brand connection and relationship quality. Issue 3 (3rd May 2016) - Dwivedi, Abhishek; Johnson, Lester W.; McDonald, Robert
Abstract : The extant literature on celebrity endorsement effects largely focuses on the endorsement effects on consumer evaluations of the endorsed brand. The current study extends the literature by assessing the impact of endorser credibility on two consumer–brand relationship-oriented outcomes – brand relationship quality and consumer self-brand connections. Additionally, the self-brand connection is positioned as a partial mediator of the effect of endorser credibility on relationship quality. A conceptual model is developed and estimated on a sample of 535 Generation Y (youth) consumers from India. The hypotheses are supported and the model demonstrates acceptable fit to the data. Overall, the present study introduces a relationship-building perspective to the celebrity endorsement literature. The results suggest that celebrity endorsers possess the ability to provide meaningful self-definitional benefits to consumers as well as cultivate enhanced relationship quality with the endorsed brands, thus contributing novel insights into celebrity endorsement dynamics.